FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN JUMLAH ANGKA KUMAN DAN KEBERADAAN ESCHERICHIA COLI PADA ALAT MAKAN (STUDI PENELITIAN DI PANTI SOSIAL ASUH KYAI AGENG MAJAPAHIT) - Kartika, Juli Arminta Sari; Yuliawati, Sri; Hestiningsih, Retno (Jurnal Kesehatan Masyarakat (Undip), 2017)
A result of data of health profile of the city of Semarang, case of diarrhea has increased from 2014 until 2015. In 2015 total cases in the age group> 5 years are 28,986 cases and lowest among age group <1 year 3,152 cases. This study was conducted with the aim of this study is to determine the factors associated with the number of germs and the presence of Escherichia coli on eating utensils in foster homes kyai ageng majapahit. This research uses quantitative with analytic observational type and cross sectional research design. The sample of this research was 44 each for spoon and plate as food swab test and 44 respondent of the food handler, then analyzed by chi-square test. Results of the microbiological examination showed 60.2% there are eating utensils containing E.coli and as much as 58% non-standard eating utensil is> 100koloni / cm2. The result of statistical test shows that there is no correlation between all variables with E.coli presence and also total number of germs in tableware at Kyai Ageng Majapahit Social Institution namely Pegetahuan (P-value 0,884; p-value 0,117), Health Condition (p-value (P-value 0,796; p-value 0,314), Drying Technique (p-value 0,543; p-value 0,732), purity value (p-value 0,702; p-value 0,702) Storage technique (p-value 0.719; p-value 0.719). The suggestion of research result of the member of a foster social institution to improve hygiene sanitation behavior either individually or jointly. Suggestions for the board of the orphanage is the need to do health checks on the 6th of the monthly children. In addition, increased knowledge of food handlers as well as infrastructure for sanitation hygiene by providing appropriate facilities.